2015
DOI: 10.9775/kvfd.2014.11693
|View full text |Cite
|
Sign up to set email alerts
|

İstanbul Yenikapı Theodosius Limanından Bizans Köpeklerinin Vücut Ağırlığı Tahmini

Abstract: In the present study, humeral and femoral midshaft circumferences were used in the weight estimation of dogs from the ancient site of the Theodosius Harbor in Istanbul. According to the calculations taken on each humerus and femur, body weight distribution of the Byzantine dogs from the Theodosius harbour was observed to be 7.953-22.385 kg. The relative ease to accommodate Terrier-size dogs in urban environments may have led to a preference for such breeds in Constantinople. It is possible that these 'light-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Although there was a scarcity of cat remains at archaeological sites dating back to the Roman period in Anatolia, for example, Didyma [20]; Pergamon [21]; Lidar Höyük [22]; Pessinus [23]; Troy [24] and Sagalassos [5], a very large assemblage of cat remains from the Yenikapi excavation site demonstrated that cats were significant in the life of the Byzantine capital city Constantinople [27,29,30]. This is an indication that the negative image of the cat during the Roman period [25] was gradually changing in the early Byzantine period as cats started to occupy a place in the social life of the Byzantine world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was a scarcity of cat remains at archaeological sites dating back to the Roman period in Anatolia, for example, Didyma [20]; Pergamon [21]; Lidar Höyük [22]; Pessinus [23]; Troy [24] and Sagalassos [5], a very large assemblage of cat remains from the Yenikapi excavation site demonstrated that cats were significant in the life of the Byzantine capital city Constantinople [27,29,30]. This is an indication that the negative image of the cat during the Roman period [25] was gradually changing in the early Byzantine period as cats started to occupy a place in the social life of the Byzantine world.…”
Section: Discussionmentioning
confidence: 99%
“…Besides of being pet animals, cats were also used in the Byzantine world to keep rodents under control [26]. Despite the scarcity of cat remains at the Roman sites in Anatolia, a very rich assemblage of cat remains from the Yenikapı Metro and Marmaray excavation demonstrated that cats played a remarkable role in the life of the Byzantine capital Constantinople [27][28][29][30]. The Yenikapı cat assemblage belongs to the Early Byzantine (4th-7th century AD) to Late Byzantine period (15th century AD) [28], and when their quantities are compared, it appears that to date, no other Byzantine site has yielded such a large assemblage of cat remains.…”
Section: Introductionmentioning
confidence: 99%
“…4) (33). Several other pathological features reflect the use of a metal curb bit of the type used by early Spanish colonists and later Mexican and Navajo craftsmen, such as the fracturing of the upper palate caused by the curb (34) and arthritis of the temporomandibular joint. Combined, these analyses indicate that early plains horses were already used for mounted riding.…”
Section: Pre-pueblo Revolt Contribution Of Horses To Indigenous Belie...mentioning
confidence: 99%